2006
DOI: 10.1242/dev.02451
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the regulatory landscape of theAbd-Bgene of the bithorax complex

Abstract: The three homeotic genes of the bithorax complex (BX-C), Ubx, abd-A and Abd-B control the identity of the posterior thorax and all abdominal segments. Large segment-specific cis-regulatory regions control the expression of Ubx, abd-A or Abd-B in each of the segments. These segment-specific cis-regulatory regions span the whole 300 kb of the BX-C and are arranged on the chromosome in the same order as the segments they specify. Experiments with lacZ reporter constructs revealed the existence of several types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(119 citation statements)
references
References 58 publications
1
118
0
Order By: Relevance
“…1A). And third, recent data have suggested that BX-C boundaries are regulated along the AP axis (Cléard et al, 2006). From these data, it seems that boundaries interact with the Abd-B promoter until the neighboring (probably more posterior) domain becomes active (see also Maeda and Karch, 2007).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…1A). And third, recent data have suggested that BX-C boundaries are regulated along the AP axis (Cléard et al, 2006). From these data, it seems that boundaries interact with the Abd-B promoter until the neighboring (probably more posterior) domain becomes active (see also Maeda and Karch, 2007).…”
Section: Resultsmentioning
confidence: 94%
“…The iab-6 enhancer region controls the level of Abd-B expression in parasegment 11 (PS11) and determines the identity of segment A6. The iab-7 region, however, controls the level of Abd-B expression in PS12 and determines the identity of segment A7 (Celniker et al, 1990;Galloni et al, 1993;Mihaly et al, 2006;Sanchez-Herrero, 1991). When Fab-7 is deleted, the iab-6 and iab-7 domains become fused into a single domain, allowing both the iab-6 and iab-7 enhancers or silencers to become active in PS11 and PS12.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the Abd-Bm expression anterior to A8 occurs at a time when the cells are refractory to posterior spiracle induction (Castelli-Gair, (iab), capable of driving expression in the Abd-B domain. iab elements are flanked by Fab boundary elements required to isolate their domains of action (Barges et al, 2000, Mihaly et al, 2006, Zhou et al, 1996. Of particular relevance for spiracle development are a 3' iab-8 and a 5' iab-8 element able to drive expression in the A8 segment from stage 9 (Estrada et al, 2002).…”
Section: Abd-b Transcriptional Regulationmentioning
confidence: 99%
“…Genetic and molecular studies have shown that each of these regulatory domains is bracketed by boundary elements Mcp, and AB-I; Fig. 1A) (Celniker et al, 1990;Gyurkovics et al, 1990;Galloni et al, 1993;Karch et al, 1994;Kyrchanova et al, 2008Kyrchanova et al, , 2011Kyrchanova et al, , 2016McCall et al, 1994;Mihaly et al, 1997Mihaly et al, , 2006Barges et al, 2000;Iampietro et al, 2010;Bender and Lucas, 2013;Bowman et al, 2014). BX-C boundaries have two important functions : one is to block crosstalk between adjacent regulatory domains; the other is bypass activity, i.e.…”
Section: Introductionmentioning
confidence: 99%